Emotional dependence of students of medicine - Zárate-Depraect, Nikell E. (2022)
Objective: To determine the emotional dependence of students of medicine in a public university. Methods: A cross-sectional study was carried-out applying the 42-item scale of emotional dependence of Ancima, Caballero, Cirilo y Aguirre (2013) with dichotomous responses (yes/no); 332 five-year medical students were selected; a non- probabilistic sample of 303 students was finally recruited. Results: 183 (60.39%) were females: mean age was 24 years; only 2.98% were stables and 90.39% had a tendency for dependence. Conclusions: Five-year medical students had a marked tendency for dependence, especially female students.